The industry of evangelism printing for the Reformation in Martin Luther's Wittenberg - Thomas, Drew B.; University of St Andrews; Brill NV (Leiden Boston Brill, 2022)
The Beginnings of the Reformation Print Industry -- The Title Page Borders of Lucas Cranach -- Fraud in the Reformation Book Trade -- The Second Generation of Reformation Printers -- Bibles and Broadsheets -- Appendix 1: A Catalogue of Wittenberg Counterfeits -- Appendix 2: USTC - VD16 Concordance.
"Of the leading print centres in early modern Europe, Wittenberg was the only one that was not a major centre of trade, politics, or culture. This monograph examines the rise of the Wittenberg printing industry and analyses how it overtook the Empire's leading print centres. It investigates the workshops of the four leading printers in Wittenberg during Luther's lifetime: Nickel Schirlentz, Josef Klug, Hans Lufft, and Georg Rhau. Together, these printers conquered the German print world"--
"This book is the result and expansion of my doctoral thesis submitted at the University of St Andrews on 31 October 2017, the date commemorating the quincentenary of Martin Luther's 'Ninety-Five Theses' and the Protestant Reformation." (Acknowledgements, Seite VII)
Literaturverzeichnis Seite [297]-325
Mit Register
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Printing -- Germany -- Wittenberg (Saxony-Anhalt) -- History -- 16th century; Christian Literature -- Publishing -- Germany -- History -- 16th century; Book industries and trade -- Germany -- History -- 16th century; Illustration of books -- Germany -- 16th century; Reformation -- Germany -- Wittenberg (Saxony-Anhalt); Wittenberg (Saxony-Anhalt, Germany) -- Imprints; Hochschulschrift